Money And Research Revolution In The Biomedical Industry: Is It A Real Race? (2016)
Medicine is a dynamic science and discipline, which arise from the human need to face the suffering, pain and give hopes for better life. Since its inception, medicine has entered a career development that has brought great advances in science. Medicine has become one of the most promising businesses in the economic field, and up today, and it is considered one of the greatest science futures with wide range of prospects.